[tex]\textit{Cofunction Identities} \\\\ sin\left(\theta-\frac{\pi}{2}\right)=-cos(\theta) \qquad\qquad cos\left(\theta-\frac{\pi}{2}\right)=+sin(\theta) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ tan\left(\frac{x}{2}~~ - ~~\frac{\pi }{2} \right)~~ = ~~\sqrt{2}\qquad \qquad \qquad \stackrel{\textit{let's make for a second}}{\cfrac{x}{2}=\theta } \\\\[-0.35em] ~\dotfill[/tex]
[tex]tan\left(\theta-\frac{\pi}{2}\right)\implies \cfrac{sin\left(\theta-\frac{\pi}{2}\right)}{cos\left(\theta-\frac{\pi}{2}\right)}\implies \cfrac{-cos(\theta )}{+sin(\theta )}\implies -cot(\theta )\implies -cot\left( \frac{x}{2} \right)[/tex]
[tex]-cot\left( \frac{x}{2} \right)~~ = ~~\sqrt{2}\implies cot\left( \frac{x}{2} \right)=-\sqrt{2} \\\\\\ cot^{-1}\left[ cot\left( \frac{x}{2} \right) \right]=cot^{-1}\left(-\sqrt{2} \right)\implies \cfrac{x}{2}=cot^{-1}\left(-\sqrt{2} \right) \\\\[-0.35em] ~\dotfill\\\\ ~\hfill x=2\left[ cot^{-1}\left(-\sqrt{2} \right) \right]~\hfill[/tex]